2012
DOI: 10.1016/j.drugalcdep.2012.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Neighborhood context and substance use disorders: A comparative analysis of racial and ethnic groups in the United States

Abstract: Background There is evidence that ethnic/racial minorities are conferred differential risk for substance use problems based on where they live. Despite a burgeoning of research focusing on the role of neighborhood characteristics on health, limited findings are available on substance use. Our study uses nationally representative data (N= 13, 837) to examine: (1) What neighborhood characteristics are associated with risk of substance use disorders?; (2) Do the associations between neighborhood characteristics a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
56
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 62 publications
1
56
1
Order By: Relevance
“…Recently, research in the UK and US identified low socio-economic class and poverty as the main factors of mental illness (Tobler et al, 2013, Lê Cook et al, 2011, similar to studies in the US examining ethnic minority populations in substance misuse (Field et al, 2012, Molina et al, 2012. The US research focus was on socio-economic factors, making drug users from poorer backgrounds more vulnerable to contracting HIV and Hepatitis C.…”
Section: Previous Researchmentioning
confidence: 91%
See 4 more Smart Citations
“…Recently, research in the UK and US identified low socio-economic class and poverty as the main factors of mental illness (Tobler et al, 2013, Lê Cook et al, 2011, similar to studies in the US examining ethnic minority populations in substance misuse (Field et al, 2012, Molina et al, 2012. The US research focus was on socio-economic factors, making drug users from poorer backgrounds more vulnerable to contracting HIV and Hepatitis C.…”
Section: Previous Researchmentioning
confidence: 91%
“…More up-to-date research on ethnicity and drug use in the US shows that research does inform and improve practice (Field et al, 2012: Molina et al, 2012: Daniulaityte et al, 2012. It identifies how ethnic groups have different needs when presenting to drug services and that their treatment packages need to be tailored to achieve effective outcomes (Daniulaityte et al, 2012).…”
Section: Previous Researchmentioning
confidence: 99%
See 3 more Smart Citations